2013
DOI: 10.1002/chem.201204322
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of Pyrazoles through a Four‐Step Cascade Sequence

Abstract: A one-pot synthesis of 3,4,5- and 1,3,5-pyrazoles from tertiary propargylic alcohols and para-tolylsulfonohydrazide has been accomplished. The pyrazoles are formed through a four-step cascade sequence, including FeCl3 -catalyzed propargylic substitution, aza-Meyer-Schuster rearrangement, base-mediated 6π electrocyclization, and thermal [1,5] sigmatropic shift. In this reaction, the 3,4,5- and 1,3,5-pyrazoles are produced selectively according to different substituents in the starting alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…124 This outcome is explained by the fact that elimination of TsNHTMS leading to the cyanation cannot occur in this situation. Instead, p-toluenesulfinic acid is eliminated and the resulting diazo compound cyclizes to the pyrazole followed by a [1,5]-sigmatropic aryl shift.…”
Section: Scheme 11mentioning
confidence: 94%
“…124 This outcome is explained by the fact that elimination of TsNHTMS leading to the cyanation cannot occur in this situation. Instead, p-toluenesulfinic acid is eliminated and the resulting diazo compound cyclizes to the pyrazole followed by a [1,5]-sigmatropic aryl shift.…”
Section: Scheme 11mentioning
confidence: 94%
“…Short time later, the same authors developed a synthesis of pyrazoles based on similar starting materials 285 (Scheme 71). [126] The difference was that, immediately after the aza ‐MSR, they heated the reaction mixture with a base. Extensive screening showed that Cs 2 CO 3 , and also K 2 CO 3 , were the most efficient bases.…”
Section: The Aza‐meyer‐schuster Rearrangementmentioning
confidence: 99%
“…7 We have also developed a one-pot synthesis of pyrazoles from the same starting materials through a four-step cascade sequence (Scheme 1, d). 8 More recently, Chen and co-workers reported the Y(OTf) 3 -catalyzed stereoselective synthesis of α,βunsaturated hydrazones from tertiary propargylic alcohols and p-toluenesulfonyl hydrazide (Scheme 1, b). 9 As part of our ongoing efforts to expand the synthetic utility of tertiary propargylic hydrazides, we report a highly efficient FeCl 3 -catalyzed substitution of tertiary propargylic alcohols to give propargylic hydrazides, and the synthesis of iodo-3H-pyrazoles (Scheme 1, e).…”
Section: Letter Syn Lettmentioning
confidence: 99%